Synthesis of monodisperse silver nanoparticles for antibacterial purposes - Adam, Sarah (Department of Chemical Engineering, 2019)
Safe drinking water is a scarcity for many in the developing world. Currently, 884 million people, 48% of whom live in sub-Saharan Africa, are without access to even basic drinking-water services (WHO/UNICEF Joint Monitoring Programme for Water Supply and Sanitation, 2017). This has a severe impact on the health of those living in such communities, which is why the universal access to safe and affordable drinking water has been made a priority by the United Nations. There is an undeniable need for change so that the lives of these many millions of people may be improved. Silver nanoparticles have great potential in being used in water disinfection applications because of their high antibacterial activity and broad antimicrobial spectrum (Qu, Alvarez, & Li, 2013). Development in this area is critical, particularly in advancing technology to allow greater accessibility to clean drinking water for people in poor, rural areas in developing countries. Incorporating nanotechnology into current water disinfection systems, as well as developing new water treatment nanotechnology, shows promise in addressing this issue. However, much research needs to be done first before this can become a reality (Q. Li et al., 2008). There is particular concern about the toxicity aspects of silver nanoparticles, both in humans and towards the environment. Whilst the current study does not investigate their toxicity, it is important to highlight the need to fully understand the human and environmental impacts nanoparticles may have in assessing their applicability in microbial control. Literature indicates that, although the role of silver nanoparticles themselves in the antibacterial mechanism cannot be excluded entirely, it is the silver ions that are mostly responsible for their antibacterial activity (Foldbjerg, Jiang, Miclăuş, et al., 2015; Le Ouay & Stellacci, 2015; Panacek et al., 2006; Xiu, Zhang, Puppala, Colvin, & Alvarez, 2012). Sotiriou & Pratsinis (2010) found that silver nanoparticles of smaller than 10 nm had a negligible antibacterial effect in comparison to the ions they released. Thus, to isolate just the effect of the released silver ions, it was desired to prepare uniformly sized particles of smaller than 10 nm. Controlling the size of the formed particles requires consideration of parameters that affect their nucleation and growth (Thanh et al., 2014). These can be thermodynamic, kinetic or stoichiometric parameters. It is on this basis that the work described herein was developed. This study aimed to synthesise silver nanoparticles suitable for use in water disinfection applications by exploring how preparation conditions affect the particle size and distribution. To do this, two different aqueous chemical reduction preparation methods were performed and reaction conditions such as surfactant concentration, agitation rate, synthesis temperature, and method of chemical addition were varied to produce monodisperse silver nanoparticles with an average size of smaller than 10 nm. This study also aimed to investigate the antibacterial efficacy of silver nanoparticles deposited on quartz fibre filters against E. coli. Two silver nanoparticle syntheses procedures were extensively investigated. Method One (AL-Thabaiti et al, 2008) uses ascorbic acid as the reducing agent and SDS (sodium dodecyl sulphate) as the surfactant whilst Method Two (Yang, Yin, Jia, & Wei, 2011) uses aniline as the reducing agent, DBSA (dodecylbenzenesulfonic acid) as the surfactant and NaOH (sodium hydroxide) as the ‘activating’ chemical. The surfactant concentrations, agitation rates, synthesis temperature, reducing agent concentrations and methods of chemical addition were varied for each of these synthesis procedures and the effect thereof on particle size was investigated. Both synthesis methods produced fcc metallic silver nanoparticles with (111) and (200) lattice planes, confirmed by studying nanoparticle d-spacings. For Method One, the unaltered synthesis procedure produced the smallest particles with a numberbased mean size of 3.6 ± 3.8 nm and a volume-based mean particle size of 15.4 ± 6.4 nm. For Method Two, which is performed at 90 °C, the ‘hot’ injection of NaOH into the system resulted in the production of the smallest nanoparticles with a number-based mean particle size of 6.7 ± 5.4 nm and a volumebased mean particle size of 22.3 ± 10.9. Removing excess surfactant and collecting these nanoparticles in powder form would facilitate antibacterial efficacy studies, however this proved to be difficult. Additionally, the presence of large nanoparticles in both samples, as evidenced from the volume-based size distributions, means that in assessing antibacterial activity of the nanoparticles, it will be difficult to interpret whether the bactericidal effect is due to silver ions or because of an interaction between the bacteria and the actual nanoparticles. Antibacterial efficacy studies were therefore not performed on these synthesised silver nanoparticles. Silver nanoparticles deposited on quartz fibre filters via spark ablation were prepared at Delft University of Technology. SEM revealed that the deposited nanoparticles on the filters had a mean particle size ranging from 25 to 70 nm. Studies using E. coli (ATCC® 25922™) did not conclusively demonstrate antibacterial activity of the filters. It is believed the large particle size, and thus slow dissolution into silver ions, may be the reason for the lack of evidence of bactericidal activity over the 24-hour experimental period. The results of this study indicate how small changes in synthesis parameters can have a significant effect on nanoparticle size and uniformity, morphology, and degree of agglomeration. This reveals the importance in specifying exact parameters used in nanoparticle preparation to allow for better reproducibility, including vessel size, mixing speed, and rate of chemical addition. This work also showed that it is important to quantify the release of silver ions from silver nanoparticles before performing antibacterial efficacy assessments. Since silver ions are the most important factor in the antibacterial action of silver nanoparticles, understanding their rate of release will allow for improved experimental design thus producing useful results. There is great potential for the use of silver nanoparticles for disinfection, as evidenced particularly by the antibacterial efficiency of Ag+ against E. coli (ATCC® 25922™). However, improvements in both the synthesis of silver nanoparticles and methods of assessing their bactericidal efficacy are clearly necessary. This study has highlighted the challenges that may be faced in the pursuit of efficiently and safely using silver nanoparticles for water treatment and disinfection. Numerous recommendations for future studies have been put forward. These include: further optimisation of the nanoparticle synthesis procedure so as to produce particles of the desired size and acquire them in powder form, performing a thermodynamic estimation of the equilibrium silver ion concentration as a function of silver nanoparticle size to quantify the effect nanoparticle size will have on bactericidal activity, and using more realistic water conditions for antibacterial efficacy experiments to simulate the environment in which silver nanoparticles will be applied.